2006
DOI: 10.1074/jbc.m512865200
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Family C G-protein-coupled Receptors by the Tripeptide Glutathione

Abstract: The Family C G-protein-coupled receptors include the metabotropic glutamate receptors, the ␥-aminobutyric acid, type B (GABA B ) receptor, the calcium-sensing receptor (CaSR), which participates in the regulation of calcium homeostasis in the body, and a diverse group of sensory receptors that encompass the amino acidactivated fish 5.24 chemosensory receptor, the mammalian T1R taste receptors, and the V2R pheromone receptors. A common feature of Family C receptors is the presence of an amino acid binding site.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
86
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(99 citation statements)
references
References 40 publications
0
86
0
Order By: Relevance
“…Among the class C G-protein-coupled receptors, the CaSR has the highest homology with GPRC6A. It has been reported that a chimeric receptor consisting of the goldfish 5.24 (mammalian GPRC6A homolog) outer membrane domain and the mouse GPRC6A trans-and intramembrane domains is activated by GSH but that neither a chimeric receptor consisting of the GPRC6A outer membrane domain and 5.24 trans-and intramembrane domains nor full-length GPRC6A itself is functionally active (28). Wellendorph et al (30) reported that GPRC6A is expressed in rat taste bud-containing epithelia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the class C G-protein-coupled receptors, the CaSR has the highest homology with GPRC6A. It has been reported that a chimeric receptor consisting of the goldfish 5.24 (mammalian GPRC6A homolog) outer membrane domain and the mouse GPRC6A trans-and intramembrane domains is activated by GSH but that neither a chimeric receptor consisting of the GPRC6A outer membrane domain and 5.24 trans-and intramembrane domains nor full-length GPRC6A itself is functionally active (28). Wellendorph et al (30) reported that GPRC6A is expressed in rat taste bud-containing epithelia.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al (28) reported that GSH does not directly activate the CaSR but potentiates calcium-induced responses. They showed that GSH does not activate the CaSR in an assay buffer containing 0.5 mM calcium, but activation occurred under similar conditions when the assay buffer was supplemented with an additional 0.3 mM calcium administered simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…S1). The results indicate that ␥-glutamyl peptides and S-methylgluta- (14) and glutathione (21) binding sites to the VFT domain and we previously identified T145A/S170T as a double mutant form of the VFT domain with near-normal Ca 2ϩ o -sensitivity but markedly impaired L-amino acid sensing (15). In the current study, we first confirmed that this mutant exhibited normal or near-normal Ca 2ϩ o sensitivity in the absence of L-Phe or S-methylglutathione (Fig.…”
Section: Effects Of ␥-Glutamyl Peptides On Camentioning
confidence: 80%
“…In addition, the CaR binds socalled type-II calcimimetics, which are typically uncharged organic compounds that act as positive allosteric modulators. Two main sites for the binding of positive allosteric modulators have been identified: one in the heptahelical domain for type-II calcimimetics such as the phenylalkylamines NPS R-467 and cinacalcet (30,32); and one or more in the VFT domain for L-amino acids such as L-Phe or L-Trp (14) and glutathione and analogs (21). Previous work suggested that the L-amino acid binding site is selectively disabled by the double mutant T145A/S170T (15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation